انخفاض الضغط داخل المقلة بعد تصنيع التربيق الانتقائي بالليزر في الزرق البدئي مفتوح الزاوية - جلول, قحطان (Latakia University Journal -Medical Sciences Series, 2013)
إن الهدف من هذه الدراسة السريرية هو التحقق من انخفاض الضغط داخل المقلة بعد تصنيع التربيق الانتقائي بالليزر في مرضى الزرق البدئي مفتوح الزاوية. أجريت الدراسة في مشفى الأسد الجامعي في جامعة تشرين باللاذقية في الفترة الممتدة من شباط 2009 حتى شباط 2011. تمت معالجة خمسين عيناً مع زرق بدئي مفتوح الزاوية غير مضبوط بواسطة ياغ ليزر مضاعف التواتر (532 نانومتر).تضمن نمط المعالجة تطبيق 50 حرقاً على امتداد 180 درجة من شبكة التربيق بطاقة تتراوح بين 0.40 و 0.92 ميلي جول في النبضة.تم تطبيق الأدوية الخافضة للضغط بعد المعالجة بالليزر كما قبل المعالجة.تم قياس الضغط داخل المقلة قبل المعالجة و في الأيام 1 و 7 بعد المعالجة، ثم بعد 1 و 3 و 6 و 12 شهر بعد المعالجة .كان الضغط الوسطي قبل المعالجة 22.48 مم ز. وكان معدل الانخفاض في نهاية الشهر الأول 4.86 مم ز (21.6 %), وبعد 3 أشهر 5.66 مم ز (25.2 %), وبعد 6 أشهر5.06 مم ز (22.5%), وبعد 12 شهر 4.92 مم ز (21.9%).وبذلك يمكن الاستنتاج أن تصنيع التربيق الانتقائي بالليزر يمثل طريقة جديدة و فعالة لخفض الضغط داخل المقلة في مرضى الزرق البدئي مفتوح الزاوية. The aim of this clinical study was to investigate the intraocular pressure (IOP) reduction after selective laser trabeculoplasty (SLT) in patients with primary open-angle glaucoma (POAG). The research has been done in Alassad Hospital, Tishreen university, Lattakia, from Feb 2009 to Feb 2011. Fifty eyes with uncontrolled POAG were treated with a frequency doubled, Q-switched Nd:YAG laser (532 nm).The pattern of treatment was applying approximately 50 burns to 180 degrees of the trabecular meshwork at energy levels ranging from 0.40– 0.92 mJ per pulse. After SLT eyes were maintained with the identical hypotensive medical therapy as that before treatment. IOP was measured before treatment, 1 and 7 days after treatment and 1, 3, 6 and 12 months after treatment. The mean pretreatment IOP was 22.48 (SD 1.84) mmHg. At the end of 1 month follow-up period the mean reduction of IOP was 4.86 mmHg (21.6%); after 3 months the mean reduction was 5.66 mmHg (25.2%); after 6 months the mean reduction of IOP was 5.06 mmHg (22.5%); at the end of 12 months follow-up period the mean reduction was 4.92 mmHg (21.9%). It can be concluded that SLT presents a new and effective method of IOP reduction in the treatment of POAG.